Selective Photooxidation and Photoreduction Processes at 𝐓𝐢𝐨𝟐 Surface-Modified by Grafted Vanadyl - Rossano Amadelli; Luca Samiolo; Andrea Maldotti; Alessandra Molinari; Delia Gazzoli (International Journal of Photoenergy)
Titanium dioxide was surface-modified by grafting vanadyl species using vanadyl triisopropoxide as a precursor. The resulting material, (VOx)n/TiO2, was characterized by Raman spectroscopy and photoelectrochemical methods. Photocatalytic oxidation of benzyl alcohol and cyclohexene were used to test oxidation selectivity and 4-nitro-benzaldehyde to assess selective photoreduction. The surface-modified TiO2 exhibits an enhanced selectivity to benzaldehyde in the photocatalytic oxidation of benzyl alcohol in an aqueous medium and an increase of cyclohexenol formation in the case of cyclohexene in nonaqueous solvent. The salient result is the 100% selective reduction of the nitrogroup in 4-nitro-benzaldehyde achieved under mild experimental conditions.